One-step synthesis of carbon sphere@ 1 T-MoS2 towards superior antiwear and lubricity. (December 2022) - Xie, Mengxin; Pan, Bingli; Liu, Hongyu; Li, Ning; Chen, Zhe; Yan, Junjiang; Fu, Zhaohui; Guo, Shihao; Wang, Honggang
Abstract: A novel carbon sphere (CS)@metallographic molybdenum disulfide (1 T-MoS2 ) hybrid was prepared by a straightforward one-step hydrothermal method and its synergistic effect on the tribology of polyethylene glycol 200 (PEG200) was reported. Systematical characterizations exhibited 1 T-MoS2 sheets were evenly anchored on the CS surface. Tribological results showed the friction coefficient of pure PEG200 oil decreased by 43% with adding 0.3125 wt% CS@ 1 T-MoS2 . Optical images showed the diameters of wear marks were significantly reduced from 1860 µm for neat base oil to 880 µm for CS@ 1 T-MoS2 . It was believed that the synergy between CS and 1 T-MoS2 played the crucial role in the friction reducing and anti-wear. Therefore, this work provides a facile approach to preparing lubricating additives by decorating 1 T-MoS2 on CS. Graphical Abstract: The evolution trends of MWD and COF in PEG200 oil in the presence of nano additives. (Inset shows its corresponding morphologies by TEM and SEM images). ga1 Highlights: A novel CS@ 1 T-MoS2 hybrid was prepared by a facile hydrothermal method. The binary hybrid exhibits superior antiwear and lubricity performances. 1 T-MoS2 sheets were evenly anchored on the CS surface, forming a chrysanthemum flower-shaped structure. The MWD was significantly reduced from 1860 µm for the base oil to 880 µm for CS@ 1 T-MoS2.